20 year-follow up of mitral stenosis patients after percutaneous valve commissurotomy: moderate disease of other valves as predictor for re-intervention. (3rd October 2022) - Amador, A; Martins Da Costa, C; Calvao, C; Pinto, R; Proenca, T; Carvalho, J M; Cabrita, A; Marques, C; Pinho, A; Santos, L; Oliveira, C; Palma, P; et al.
Abstract: Background: Percutaneous valve commissurotomy (PMC) is a viable alternative to mitral valve (MV) surgery in the treatment of patients with clinically significant mitral stenosis (MS). About 40% of patients treated with PMC will require at least one reintervention (either PMC or MVS) along time. Purpose: To evaluate the long-term results of PMC in patients with rheumatic MS. Methods: We retrospectively analysed all consecutive patients between 1991 and 2008 with clinically significant rheumatic MS undergoing PMC. Clinical and echocardiographic data were collected at baseline and during early and long-term follow-up. MACE was a composite of adverse events defined as all-cause mortality, MV re-intervention or cardiovascular hospitalization. Results: A total of 124 patients were enrolled: 108 (87%) were female, with a mean age at the time of PMC of 46±11 years. At baseline, 34% patients were in NYHA class ≥ III and 81% had a Wilkins score ≤8; all patients had preserved biventricular systolic function and 83% presented pulmonary hypertension. Regarding associated valve disease, 46 patients had mild tricuspid regurgitation (TR), 19 mild aortic regurgitation (AR), 14 moderate IT and 5 moderated AR. Most of the procedures were successful (91%) and without complications (94%), with median improvement in MV area of 0.9 cm 2 (IQR 0.5) and median reductions in mean transmitral gradient (MTG) of 6 mmHg (IQR 6) and in pulmonary artery systolic pressure (PASP) of 8 mmHg (IQR 10) early after PMC. During the mean follow-up of 20±6 years, 52 (42%) of patients had MV re-intervention (86% surgery and 14% re-PMC), 37 (30%) were hospitalized and 30 (24%) died. Concerning time-to-event analysis, approximately 80% of patients kept MACE-free after 10 years; after 30 years, more than 20% continued MACE-uneventful, approximately 50% were alive and about 45% were free from re-intervention. Considering patients submitted to surgical re-intervention, 9 underwent MV valvuloplasty and the others MV replacement with mechanical (32) or biological prothesis (11). At the same procedure, 23 patients were submitted to tricuspid annuloplasty, 9 to other valve replacement and one to coronary artery bypass graft. Using Cox regression, we found that the presence of moderate disease of other valves at PMC time was associated with a 2.3-fold greater rate of re-intervention compared to patients with none or mid disease of other valves (HRcrude 2.3; 95% IC 1.221–4.331, p=0.017). After adjusting for the success of the PMC and for mitral regurgitation after PMC, the observed effect remained significant (HRadjusted = 2.7; 95% CI 1.417–5.233, p=0.003). Conclusion: PMC was safe and effective in clinically significant rheumatic MS. Most of the patients were free from adverse events after 10 years and half were alive after 30 years. Still, about 40% required re-intervention, with moderate disease of other valves as its independent predictor. Funding Acknowledgement: Type of funding sources: None.